Effects of oil exposure, plant species composition, and plant genotypic diversity on salt marsh and mangrove assemblages. Issue 4 (24th April 2018) - Hughes, A. R.; Cebrian, J.; Heck, K.; Goff, J.; Hanley, T. C.; Scheffel, W.; Zerebecki, R. A.
Abstract: Climate change is causing shifts in the distribution and abundance of many species. Because species vary in the rate and degree of these shifts, novel transition zones have developed where new combinations of species overlap. If climate‐mediated range shifts result in greater diversity, transition communities could have enhanced resistance and/or resilience, particularly if the resident and colonizing species differ in their response to environmental change. The range expansion of the tropical black mangrove, Avicennia germinans, into salt marshes dominated by the temperate cordgrass, Spartina alterniflora, provides an opportunity to examine the responses of climate‐mediated transition zones to disturbance. We conducted a yearlong mesocosm experiment testing the effects of plant species identity and composition ( A. germinans, S. alterniflora ), as well as plant genotypic diversity ( S. alterniflora only), on the response of coastal wetlands to oiling disturbance. Oil negatively impacted S. alterniflora and A. germinans both above‐ and belowground, though the timing of these effects varied, with S. alterniflora showing more immediate declines than A. germinans . As hypothesized, the magnitude of the oil effect was reduced in the mixed plant species treatment compared to the single species treatment for A. germinans survival (12% vs. 21% reduction) and belowground biomass (19% vs. 71% reduction). In addition, when exposed to oil, A. germinans crown area and volume were greater in the mixed species treatment compared to the single species treatment at the end of the experiment. However, we did not detect any benefit of mixed species communities or S. alterniflora genotypic diversity for the S. alterniflora response to oil. Our results suggest that transition habitats in the northern Gulf of Mexico where A. germinans and S. alterniflora co‐occur will be negatively impacted by future oiling events, but that they are no more susceptible, and perhaps slightly less so, than habitats dominated by either individual species.